Numerical and Experimental Investigation on the Aerodynamic performance of roller Airfoil - Senthil Kumar, M.; Vijayanandh, R.; Kaviarasan, N.; Dinesh Kumar, R.; Adrin Issai Arasu, I.; Kanmaniraja, R. (International Journal of Engineering and Technology, 2018)
Prevailing norm is a fixed wing in a conventional aircraft, but the prospect appears bright for developing wings that could yield better aerodynamic properties with a change in the form and shape, this may have a wider application in future aviation. The main objective of this paper is to probe such a morphing technology in wings to improve their aerodynamic performance while operating at various cruise conditions. The airfoil is equipped with a rolling mechanism on its upper surface, operated by custom- designed controllers. This roller airfoil model will generate higher lift at low angles of attack and substantially increase flight performance, leading to the evolution of a create multiple-regime, aerodynamically efficient aircraft. This paper aims to compare the performance enhancement of roller airfoil over a conventional airfoil, by increasing the velocity at the upper surface of the airfoil to increase the lift to drag ratio using typical engineering analyses. The cambered airfoil chosen here is NACA 4412. Morphing concept brings about the improvement due to a reduction in lift-induced drag by promoting large laminar flow run on the upper surface of the wing.Â Â